Structure and properties of the giant reed (Arundo donax) lectin (ADL). (29th June 2021) - Perduca, Massimiliano; Bovi, Michele; Destefanis, Laura; Nadali, Divina; Fin, Laura; Parolini, Francesca; Sorio, Daniela; Carrizo, Maria E; Monaco, Hugo L
Abstract: Arundo donax lectin (ADL) is a 170 amino acid protein that can be purified from the rhizomes of the giant reed or giant cane by exploiting its selective binding to chitin followed by elution with N -acetylglucosamine. The lectin is listed in the UniProt server, the largest protein sequence database, as an uncharacterized protein with chitin-binding domains (A0A0A9P802). This paper reports the purification, structure and ligand-binding properties of ADL. The lectin is a homodimer in which the two protomers are linked by two disulfide bridges. Each polypeptide chain presents four carbohydrate-binding modules that belong to carbohydrate-binding module family 18. A high degree of sequence similarity is observed among the modules present in each protomer. We have determined the X-ray structure of the apo-protein to a resolution of 1.70 Å. The carbohydrate-binding modules, that span a sequence of approximately 40 amino acids, present four internal disulfide bridges, a very short antiparallel central beta sheet and three short alpha helices, two on one side of the beta sheet and one on the other. The structures of the complexes of the lectin with N -acetylglucosamine, N -acetyllactosamine, N -acetylneuraminic acid and N - N 'diacetylchitobiose reveal that ADL has two primary and two secondary carbohydrate-binding sites per dimer. They are located at the interface between the two protomers, and each binding site involves residues of both chains. The lectin presents structural similarity to the wheat germ agglutinin family, in particular, to isoform 3.